Back Cover: Alternating Copolymer of Double Four Ring Silicate and Dimethyl Silicone Monomer–PSS‐1 (Chem. Eur. J. 47/2017). Issue 47 (18th July 2017) - Smet, Sam; Vandenbrande, Steven; Verlooy, Pieter; Kerkhofs, Stef; Breynaert, Eric; Kirschhock, Christine E. A.; Martineau‐Corcos, Charlotte; Taulelle, Francis; Van Speybroeck, Veronique; Martens, Johan A.
Abstract : Systematic linking of double four‐ring (D4R) silicate units through their corners with dimethylsilicone monomers creates a new silicate–silicone copolymer named PSS‐1 (polyoligosiloxysilicone number one). PSS‐1, which consists of twisted columns of D4R units bridged by dimethylsilicone, shows exceptional thermal stability and mechanical strength. This new polymer is the first member of a new class of materials termed Posisils synthesized from pre‐shaped silicate units and silicone linkers. More information can be found in the Full Paper by J. A. Martens et al. onpage 11286 .